Effect of low doses of bezafibrate and fenofibrate on liver 2-oxo-glutarate dehydrogenase complex in low-protein diet fed rats (Bangladesh Journal of Pharmacology, 2015)
Multienzyme 2-oxoglutarate complex (2-OGDH) together with branched chain ?-ketoacid dehydrogenase (BCKDH) and pyruvate dehydrogenase  belong to the family of mitochondrial 2-oxoacid dehydrogenases. Hypolipidemic drugs, bezafibrate and fenofibrate, up-regulate liver BCKDH. The present study has been undertaken to determine the effect of low doses of bezafibrate and fenofibrate on liver 2-OGDH. Fibrates were administrated to rats fed low-protein diet at 5, 10 or 20 mg/kg. In rats treated with increasing doses of bezafibrate 2-OGDH activity increased by 7, 35 and 42%, while in rats administered with fenofibrate by 8, 18, and 56% (p